Synthesis and post-functionalization of alternate-linked-meta-para-[2n.1n]thiacyclophanes - De Leger, Wout; Adriaensen, Koen; Robeyns, Koen; Van Meervelt, Luc; Thomas, Joice; Meijers, Björn; Smet, Mario; Dehaen, Wim (Beilstein Journal of Organic Chemistry, 2018)
In recent decades, considerable research attention has been devoted to new synthetic procedures for thiacyclophanes. Thiacyclophanes are widely used as host molecules for the molecular recognition of organic compounds as well as metals. Herein, we report the selective and high-yielding synthesis of novel alternate-linked-meta-para-thiacyclophanes. These novel thiacyclophanes are selectively synthesized in high-yielding procedures. Furthermore, post-functionalization of the phenolic moieties was successfully performed. The 3D structure of the alternate-linked-meta-para-[22.12]thiacyclophane was further elucidated via X-ray crystallographic analysis.
Keywords: alternate-linked-meta-para-bridge; cyclocondensation; heteramacrocycles; o-quinoid intermediate; thiacyclophanes